2024
DOI: 10.1002/pca.3333
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profiling and quality evaluation of Liuweizhiji Gegen‐Sangshen oral liquid by UPLC‐Q‐TOF‐MS and HPLC‐diode array detector fingerprinting

Shulin Wei,
Yu Jiang,
Mingxing Li
et al.

Abstract: IntroductionLiuweizhiji Gegen‐Sangshen (LGS) oral liquid is a Chinese patent medicine that is widely used for the prevention and treatment of alcoholic liver disease in clinical practice. However, the chemical complexity of LGS has not yet been investigated.ObjectiveThe aim of this study was to rapidly identify chemical constituents of LGS and establish a quality control method based on fingerprint and quantitative analysis.MethodologyA comprehensive strategy was used by combining qualitative analysis by ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…), Mori fructus (The dried fructus of Morus alba L.) and Canarli fructus (The dried fructus of Canarium album Raeusch. ), is available in market and is popular in southwest China, which has been used for alleviating alcohol-mediated discomfort and preventing alcoholic liver disease (ALD) ( 1 ). This functional drink and its components have been traditionally used to treat digestive tract disorders including liver dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), Mori fructus (The dried fructus of Morus alba L.) and Canarli fructus (The dried fructus of Canarium album Raeusch. ), is available in market and is popular in southwest China, which has been used for alleviating alcohol-mediated discomfort and preventing alcoholic liver disease (ALD) ( 1 ). This functional drink and its components have been traditionally used to treat digestive tract disorders including liver dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that some flavonoids and organic acids, including puerarin and its derivatives, vitexin, rutin and gallic acid, showed anti-oxidant, anti-inflammatory and gut microbiota regulating activities and contributed to the ALD alleviating effect of LGS ( 2–5 ). Current studies on active ingredients of LGS are mainly focused on the small-molecule components ( 1 ), however, the polysaccharide fraction is largely unexplored. The activity and quality control of polysaccharides from LGS necessitate further studies.…”
Section: Introductionmentioning
confidence: 99%